Hubungan Antara Stress Dengan Konsep Diri Pada Penderita Diabetes Mellitus Tipe 2 - Loly Irma Sofiana; Veny Elita; Wasisto Utomo (Fakultas Keperawatan, Universitas Riau, 2012)
The aim of this study is to determine the relationship between stress and self-concept in patient with type 2 diabetesmellitus. The research method used a descriptive design with cross sectional correlation. The study was conducted in theinpatient unit Arifin Achmad Pekanbaru hospital on 30 patient with type 2 diabetes using a convenience sampling techniquebased on the inclusion criteria. Research instruments used was a questionnaire with 36 statements developed by the researcher.The analysis used was univariate and bivariate analysis using Kolmogorov-Smirnov. The result showed that there is a relationshipbetween stress and self-concept in patient with type 2 diabetes with the degree of significance of 0.05 is obtained P < 0.05 is0.039. Based on the result of this research, it is expected for nurses who provide nursing care for patients with type 2 diabetesto consider the psychological aspects of patients due to severe stress levels that not only could change a negative self-conceptbut also may aggravate the patient’s illness.Keywords: type2 diabetes mellitus, self-concept, stress.